2012
DOI: 10.1002/cssc.201100695
|View full text |Cite
|
Sign up to set email alerts
|

Depolymerization and Hydrodeoxygenation of Switchgrass Lignin with Formic Acid

Abstract: Organosolv switchgrass lignin is depolymerized and hydrodeoxygenated with a formic acid hydrogen source, 20 wt % Pt/C catalyst, and ethanol solvent. The combination of formic acid and Pt/C is found to promote production of higher fractions of lower molecular weight compounds in the liquid products. After 4 h of reaction, all of the switchgrass lignin is solubilized and 21 wt % of the biomass is shown to be converted into seven prominent molecular species that are identified and quantified. Reaction time is sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(144 citation statements)
references
References 37 publications
5
136
0
3
Order By: Relevance
“…The yield of oil products increased with time and was highest after 6 h. Again based on the dry weight of lignin, oil yields more than doubled from 15.3 wt% to 33.1 wt% between 1 h and 6 h, which compares well to the work of Xu et al [20], who used formic acid and Pt/C for lignin depolymerization, although at a slightly higher temperature of 280 °C. In the opposite direction, the yield of watersoluble products decreased with time, showing that some of the water soluble products were being converted into char and extractable oil products.…”
Section: Product Yields From Lignin Depolymerizationsupporting
confidence: 83%
See 2 more Smart Citations
“…The yield of oil products increased with time and was highest after 6 h. Again based on the dry weight of lignin, oil yields more than doubled from 15.3 wt% to 33.1 wt% between 1 h and 6 h, which compares well to the work of Xu et al [20], who used formic acid and Pt/C for lignin depolymerization, although at a slightly higher temperature of 280 °C. In the opposite direction, the yield of watersoluble products decreased with time, showing that some of the water soluble products were being converted into char and extractable oil products.…”
Section: Product Yields From Lignin Depolymerizationsupporting
confidence: 83%
“…Formic and acetic acids can be produced from biomass and lignin under certain hydrothermal conditions [16][17][18] and using them for lignin processing into valuable products will improve sustainability. Besides, formic acid can easily be reformed into hydrogen [19] required for the hydrogenolysis and/or hydrodeoxygenation of lignin into valuable chemicals [20]. Xu et al [20], used formic acid (FA) for the depolymerization and hydrodeoxygenation of Organosolv lignin obtained from switch grass in the presence of 20 wt% Pt/C catalysts at 280 °C.…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Zhang et al have shown that woody lignin is catalytically hydrogenated to guaiacol and syringols at 235 C under 6 MPa H 2 , and has obtained 46% (based on lignin) phenolic compounds. 31 Other catalysts, such as CuCr oxide, 32 Co-Mo-S/Al 2 O 3 , 33 activated carbon-, alumina-or silica-supported Ru [34][35][36][37] or Pt, 38,39 have also been reported in hydrogenation of lignin or model compounds to monomeric phenols. Nickel-based catalysts have shown excellent chemoselectivity for aromatic products or high activity for C-O bond cleavage, as reported by Hartwig 40 and Rinaldi.…”
Section: Introductionmentioning
confidence: 99%
“…It has been successfully used to depolymerize various lignins into hydrodeoxygenated liquids [10,51]. By adding a Pt/C catalyst and acetic acid into ethanol, even higher yields of monomeric phenols and low amounts of char were reached from a switchgrass lignin [52].…”
Section: Solvolysis (In Organic Solvents)mentioning
confidence: 99%